Study of Lacid Acid Bacteria Activities from Human Oral Mucosa for Candida albicans Inhibition - Evi Lauw (Hasanuddin University, 2017)
Lactic acid bacteria are known to have potential in producing antimicrobial compounds, including antifungal agents. This study aims to determine whether the lactic acid bacteria from human oral mucosa have the potential to produce the secondary metabolite to inhibit the candidiasis, which caused by pathogen fungi, Candida albicans. Lactic acid bacteria were isolated from three healthy respondents based on age difference that is an infant, child, and adult. Lactic acid bacteria isolation using the deMann Rogosa Sharpe Broth (MRSB)-liquid medium, followed by purification stage with the quadrant scratch method using the deMann Rogosa Sharpe Agar (MRSA)-solid medium. The purified isolates obtained were characterized and identified by Gram staining, biochemical tests, and inhibition zone diameter measurement toward pathogenic fungi Candida albicans. The results were obtained from each of the two lactic acid bacteria isolates from each respondent with characteristics including gram-positive bacteria with short stem cell shape, possibly as Lactobacillus sp. It is conclude that the lactic acid bacteria of oral mucosa from adult had greater anticandidal activity than infant and child. Keywords: lactic acid bacteria, human oral mucosa, antifungal activity, Candida albicans